2015
DOI: 10.1186/s12992-015-0114-z
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of an electronic fingerprint-linked data collection system: a feasibility and acceptability study among Zambian female sex workers

Abstract: BackgroundPatient identification within and between health services is an operational challenge in many resource-limited settings. When following HIV risk groups for service provision and in the context of vaccine trials, patient misidentification can harm patient care and bias trial outcomes. Electronic fingerprinting has been proposed to identify patients over time and link patient data between health services. The objective of this study was to determine 1) the feasibility of implementing an electronic-fing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 30 publications
1
43
2
Order By: Relevance
“…[48] Sambasivan et al, for example, have designed a phone broadcasting system for urban sex workers in India [48] in collaboration with a charity and have improved reach and informed sex workers about health issues. Wall et al [55] have taken a healthfocus on sex work in Zambia, where it was found that fingerprint-linked patient tracking and data collection was a feasible option in resource restrained areas (although the sex workers often refused to give their fingerprints due to a perceived lack of privacy).…”
Section: Social Justicementioning
confidence: 99%
“…[48] Sambasivan et al, for example, have designed a phone broadcasting system for urban sex workers in India [48] in collaboration with a charity and have improved reach and informed sex workers about health issues. Wall et al [55] have taken a healthfocus on sex work in Zambia, where it was found that fingerprint-linked patient tracking and data collection was a feasible option in resource restrained areas (although the sex workers often refused to give their fingerprints due to a perceived lack of privacy).…”
Section: Social Justicementioning
confidence: 99%
“…This study incidentally identi ed some speci c diagnoses in which CBR workers feel they require more support, and whether assistance was most needed before, during, or after telehealth sessions, which carries its own implications for the training and support needs of CBR workers [4]. Similar to other studies completed in LMICs, this study also identi ed some cultural barriers and beliefs that might limit progression of technology use in LMIC [17].…”
Section: Discussionmentioning
confidence: 56%
“…This pilot addressed previously mentioned barriers to sustainability and scalability through qualitative evaluation of technical, operational, infrastructural, cultural and economic feasibility [11]. Similar to other studies implementing technologies that are novel to the adopting community, a training to mitigate complexity of the intervention was planned and executed [11,17]. Implementation science literature highlight the importance of technical consensus when planning for scalability [11].…”
Section: Discussionmentioning
confidence: 99%
“…Cunningham and Kendall [14] raise important legal and regulatory questions surrounding the advertising and exchanging of digitally mediated sexual encounters for this growing online market that incentivises reputation-building as well as screening practices. Furthermore, digital technologies have been designed to support peer-sharing [49], to track health information in developing contexts [67], or to support sharing of safety information [59]. What may be lacking in the current research however, is the development of digital technologies with sex workers directly that take into account their agency and skillsets.…”
Section: Chi 2019 Papermentioning
confidence: 98%